VRSEMLAB: A Low Cost Virtual Reality System to Illustrate Complex Concepts Involving Spatial Relationships - Sines, P.; Das, B. (International Journal of Virtual Reality, 2001)
Virtual Reality (VR) is a powerful education/training tool, and its interactive immersive environment is particularly suitable for the illustration of complex concepts involving spatial relationships. Although many virtual reality applications have been developed for education and training, the wide spread use of this technology has been primarily limited by the high cost of VR systems. We have developed VRSEMLAB, a low cost VR application to teach the complex subject of semiconductor device physics to undergraduate students. VRSEMLAB demonstrates an effective method for using virtual reality to model complex 3D systems in an experimental environment free of concerns of physical safety, equipment limitations, and size limitations.